Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1108/03090599910253564
|View full text |Cite
|
Sign up to set email alerts
|

Small firm organisational learning: comparing the perceptions of need and style among UK support service advisors and small firm managers

Abstract: It is increasingly the case that within the academic literature, firms seeking to survive in rapidly changing and/or highly competitive markets are being advised to consider adopting an organisational learning philosophy as a strategy through which to develop new approaches to delivering greater customer value. This view is apparently shared by the UK Government, which has incorporated the concept of Lifelong Learning into its small firms support policy. This is despite the fact that to date in the academic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 19 publications
(15 reference statements)
1
32
0
1
Order By: Relevance
“…OL is gaining increasing mention in the literature as a mechanism for assisting SME survival (Chaston et al, 1999). Due to their specificities, SMEs show a particular behaviour with regard to the creation, development, sharing, protection and transmission of knowledge (Basly, 2007).…”
Section: Organizational Learning In Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…OL is gaining increasing mention in the literature as a mechanism for assisting SME survival (Chaston et al, 1999). Due to their specificities, SMEs show a particular behaviour with regard to the creation, development, sharing, protection and transmission of knowledge (Basly, 2007).…”
Section: Organizational Learning In Smesmentioning
confidence: 99%
“…Research has shown that firms overcome learning traps by employing emerging, novel and pioneering technologies, but how learning is undertaken through these technologies is unknown (Small & Irvine, 2006). In addition, earlier studies on OL have expressed concerns about the lack of empirical research (Dawes, Lee, & Midgley, 2007;Vince, Sutcliffe, & Olivera, 2002) and have neglected small-and medium-sized enterprises (SMEs) when analyzing OL (Chaston, Badger, & Sadler-Smith, 1999). Consequently, this paper investigates the effect of ICT adoption and ICT use on OL in SMEs in order to address these issues.…”
Section: Introductionmentioning
confidence: 96%
“…Particularly relative to the endeavours of support agencies, Chaston et al (1999) emphasise that understanding the way small business owner-managers learn is the key to effective interventions. Any discussion of learning begs a definition of what it involves.…”
Section: Small Business Owner-manager Learningmentioning
confidence: 99%
“…They cannot be coerced, rarely conform to 'type', have to cope with absolute power and leadership responsibilities, and are subject to a number of competing and conflicting influences which may lead to behaviours that defy logic (Beaver et al, 1998). Also converging on the business support landscape is the concept of 'life long learning' that has been selected by a number of governments as a platform through which to communicate the need for individuals and businesses to continuously seek to learn and apply new knowledge (Chaston et al, 1999). Certainly, as economies have shifted from industrial to knowledge eras, learning for knowledge management has become recognised as the new route to sustained competitive advantage (Frey, 2000;Winterton et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation